Trust-based service innovation of municipal home care: a longitudinal mixed methods study - Tom Eide; Monika K. Gullslett; Hilde Eide; Janne H. Dugstad; Brendan McCormack; Etty R. Nilsen (BMC, 2022)
Abstract Background In Scandinavia, various public reforms are initiated to enhance trust in the healthcare services and the public sector in general. This study explores experiences from a two-step service innovation project in municipal home care in Norway, coined as the Trust Model (TM), aiming at developing an alternative to the purchaser-provider split (PPS) and enhancing employee motivation, user satisfaction, and citizen trust. The PPS has been the prevalent model in Norway since the 1990s. There is little empirical research on trust-based alternatives to the PPS in healthcare. The overall objectives of this study were to explore facilitators and barriers to trust-based service innovation of municipal homecare and to develop a framework for how to support the implementation of the TM. Methods The TM elements were developed through a comprehensive participatory process, resulting in the decision to organize the home care service in small, self-managed and multidisciplinary teams, and trusting the teams with full responsibility for care decisions and delivery within a limited area. Through a longitudinal mixed methods case study design a) patients' expressed values and b) factors facilitating or preventing the service innovation process were explored through two iterations. The first included three city districts, three teams and 80 patients. The second included four districts, eight teams and 160 patients. Results The patient survey showed patients valued and trusted the service. The team member survey showed increased motivation for work aligned with TM principles. Both quantitative and qualitative methods revealed a series of facilitators and barriers to the innovation process on different organizational levels (teams, team leaders, system). The key message arising from the two iterations is to keep patients' values in the centre and recognize the multilevelled organizational complexity of successful trust-based innovation in homecare. Synthesizing the results, a framework for how to support trust-based service innovation was constructed. Conclusions Trust-based innovation of municipal homecare is feasible. The proposed framework may serve as a tool when planning trust-based innovation, and as a checklist for implementation and improvement strategies. Further research is needed to explore the validity of the framework and its replicability in other areas of healthcare.